2014
DOI: 10.1519/jsc.0b013e3182956569
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Myofascial Release With Foam Rolling on Performance

Abstract: In the last decade, self-myofascial release has become an increasingly common modality to supplement traditional methods of massage, so a masseuse is not necessary. However, there are limited clinical data demonstrating the efficacy or mechanism of this treatment on athletic performance. The purpose of this study was to determine whether the use of myofascial rollers before athletic tests can enhance performance. Twenty-six (13 men and 13 women) healthy college-aged individuals (21.56 ± 2.04 years, 23.97 ± 3.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
176
1
35

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(225 citation statements)
references
References 20 publications
13
176
1
35
Order By: Relevance
“…Participants in this study completed single 60-second bouts rolling the thigh bilaterally (10 minutes overall) following a 10 x 10 back squat program. Healey et al (2014) have also presented an alternative hypothesis for the subjective benefit of foam rolling. These authors suggest the decrease in perceived muscle fatigue with foam rolling may be psychological.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants in this study completed single 60-second bouts rolling the thigh bilaterally (10 minutes overall) following a 10 x 10 back squat program. Healey et al (2014) have also presented an alternative hypothesis for the subjective benefit of foam rolling. These authors suggest the decrease in perceived muscle fatigue with foam rolling may be psychological.…”
Section: Resultsmentioning
confidence: 99%
“…Healey et al (2014) also used short 30-second bouts on multiple muscle groups and demonstrated no gain in vertical jump height and power, isometric force production, and agility. The equivocal results of these studies suggest that investigation of the physiological effect of the application of a foam roller, beyond increasing ROM, is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of self MTrP release in patients with triceps surae (calf) dysfunction focussing on MTrPs in the gastrocnemius and soleus using a FR in combination with a course of MTrP therapy, has also been investigated (Grieve et al 2013a). The use of a FR is often advocated in clinical practice and by fitness professionals in fields such as yoga and sports (Healey et al 2014;Okamoto et al 2014). Related research using therapist initiated myofascial release (MFR), has been identified in increasing quadriceps and hamstrings ROM (Kuruma et al 2013);chronic lower back pain (Ajimsha et al 2014a) and plantar heel pain (Ajimsha et al 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the scientific evidence of the application of the myofascial release therapy is scarce. [1][2][3][4][5][6] Since is complicated to objectify the effects of the therapy and there are different ways to apply it. Nowadays, there are also a numerous ways with different tools to self-release the myofascia after physical exercise that have not been proven enough to be effective.…”
Section: Opinionmentioning
confidence: 99%